Loss of MD1 exacerbates pressure overload-induced left ventricular structural and electrical remodelling - Jianye Peng (Nature Portfolio, 2017)
Abstract Myeloid differentiation protein 1 (MD1) has been implicated in numerous pathophysiological processes, including immune regulation, obesity, insulin resistance, and inflammation. However, the role of MD1 in cardiac remodelling remains incompletely understood. We used MD1-knockout (KO) mice and their wild-type littermates to determine the functional significance of MD1 in the regulation of aortic banding (AB)-induced left ventricular (LV) structural and electrical remodelling and its underlying mechanisms. After 4 weeks of AB, MD1-KO hearts showed substantial aggravation of LV hypertrophy, fibrosis, LV dilation and dysfunction, and electrical remodelling, which resulted in overt heart failure and increased electrophysiological instability. Moreover, MD1-KO-AB cardiomyocytes showed increased diastolic sarcoplasmic reticulum (SR) Ca2+ leak, reduced Ca2+ transient amplitude and SR Ca2+ content, decreased SR Ca2+-ATPase2 expression, and increased phospholamban and Na+/Ca2+-exchanger 1 protein expression. Mechanistically, the adverse effects of MD1 deletion on LV remodelling were related to hyperactivated CaMKII signalling and increased impairment of intracellular Ca2+ homeostasis, whereas the increased electrophysiological instability was partly attributed to exaggerated prolongation of cardiac repolarisation, decreased action potential duration alternans threshold, and increased diastolic SR Ca2+ leak. Therefore, our study on MD1 could provide new therapeutic strategies for preventing/treating heart failure.